A U.K. Cost-Benefit Analysis of Circles of Support and Accountability Interventions. (June 2013) - Elliott, Ian A.; Beech, Anthony R.
Circles of Support and Accountability (CoSA) aim to augment sex offender risk management at the point of community reentry by facilitating "Circles" of volunteers who provide support, guidance, and advice, while ensuring that the offender remains accountable for their actions. In this study, the authors provide (a) a rapid evidence assessment of the effectiveness of CoSA in reducing reoffending, and (b) a U.K. cost-benefit analysis for CoSA when compared to the criminal justice costs of reoffending. From the study analysis, the average cost of a "Circle" was estimated to be £11, 303 per annum and appears to produce a 50% reduction in reoffending (sexual and nonsexual), as the estimated cost of reoffending was estimated to be £147, 161 per offender, per annum. Based on a hypothetical cohort of 100 offenders—50 of whom receive CoSA and 50 of whom do not—investment in CoSA appears to provide a cost saving of £23, 494 and a benefit-cost ratio of 1.04. Accounting for estimates that the full extent of the cost to society may be 5 to 10 times the tangible costs substantially increases estimated cost savings related to CoSA.